Necklace-like Fe3O4 nanoparticle beads on carbon nanotube threads for microwave absorption and supercapacitors. (April 2020) - Zeng, Xiaojun; Zhu, Lingyu; Yang, Bai; Yu, Ronghai
Abstract: Commonly, one typical performance of the materials can be fully utilized in a certain field due to the particular physical or chemical properties. In this work, a multifunctional novel necklace-like three-dimension (3D) Fe3 O4 /CNTs nanocomposite with carbon nanotubes (CNTs) threading into homogeneous spherical Fe3 O4 nanoparticles have been fabricated by a one-pot hydrothermal method. The good intrinsic magnetic and dielectric properties for the 3D Fe3 O4 /CNTs nanocomposites lead to their outstanding microwave absorption performances (minimum R L value of −59.2 dB with a thin thickness of 1.68 mm). Furthermore, high electrical conductivity and fast surface redox are also observed in these Fe3 O4 /CNTs nanocomposites resulting in their excellent electrochemical properties (specific capacitance of 361.1 F g −1 at 0.5 A g −1 ). This work indicates that the distinct physical and chemical properties can be realized in the same composite structure by the suitable composite technology, which can not only improve the material utilization but also enable the preparation of multifunctional devices. Graphical abstract: Unlabelled Image Highlights: A multifunctional necklace-like 3D Fe3 O4 /CNTs nanocomposites are fabricated. The good magnetic and dielectric properties lead to outstanding microwave absorption. The high conductivity and fast surface redox resulting in excellent electrochemical properties. Fe3 O4 /CNTs exhibit extraordinary microwave absorption and supercapacitor performances.